2006
DOI: 10.2174/157016106776359835
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Management of No Reflow During Percutaneous Coronary Intervention

Abstract: Angiographic no reflow is a recognized phenomenon during percutaneous coronary intervention (PCI). It usually follows successful lesion dilation and, by definition, it represents a reduction in epicardial coronary blood flow in the absence of identifiable dissection, obstruction or distal vessel cut off (indicative of distal embolisation). No reflow appears to be more commonly associated with PCI for acute myocardial infarction and PCI for saphenous vein graft occlusions. While the exact mechanism of no reflow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 56 publications
(58 reference statements)
0
14
0
1
Order By: Relevance
“…Use of a vasodilator to treat no‐reflow was first described by Wilson et al in 1989 who reported a favorable response to papaverine in a single patient. Since this time the effect of several different vasodilators on no‐reflow has been investigated including nitrates, verapamil, adenosine, nicardipine, and sodium nitroprusside, but interestingly a vasoconstrictor‐like epinephrine may also have a role through acting on β‐receptors to produce coronary vasodilatation . This study was conducted to compare local delivery of adrenaline ± verapamil in the distal coronary bed via perfusion balloon or selective microcatheter versus intracoronary route through the guiding catheter regarding safety and efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Use of a vasodilator to treat no‐reflow was first described by Wilson et al in 1989 who reported a favorable response to papaverine in a single patient. Since this time the effect of several different vasodilators on no‐reflow has been investigated including nitrates, verapamil, adenosine, nicardipine, and sodium nitroprusside, but interestingly a vasoconstrictor‐like epinephrine may also have a role through acting on β‐receptors to produce coronary vasodilatation . This study was conducted to compare local delivery of adrenaline ± verapamil in the distal coronary bed via perfusion balloon or selective microcatheter versus intracoronary route through the guiding catheter regarding safety and efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…As the process is multifactorial, various therapeutic strategies are required in different situations. Current pharmacological management involves the use of vasodilators, including nitrates, verapamil, papaverine, adenosine, nicardipine, and sodium nitroprusside, but interestingly, vasoconstrictors such as epinephrine may also have a role . Verapamil is a calcium channel blocker (CCB) that improves vascular wall stress and increases myocardial perfusion by disrupting the movement of calcium (Ca 2+ ) through calcium channels in coronary arteries .…”
Section: Introductionmentioning
confidence: 99%
“…of vasodilators, including nitrates, verapamil, papaverine, adenosine, nicardipine, and sodium nitroprusside, but interestingly, vasoconstrictors such as epinephrine may also have a role. 3 Verapamil is a calcium channel blocker (CCB) that improves vascular wall stress and increases myocardial perfusion by disrupting the movement of calcium (Ca 2+ ) through calcium channels in coronary arteries. 4 Based on the mechanism of action of verapamil, this CCB agent has been widely used in catheter labs to prevent and treat coronary no-reflow.…”
Section: Introductionmentioning
confidence: 99%
“…As the processes for no‐reflow and PMI are multifactorial, various therapeutic strategies are required in different situations. Current pharmacological management involves the use of antiplatelet agents, vasodilators, and statins …”
Section: Introductionmentioning
confidence: 99%
“…Current pharmacological management involves the use of antiplatelet agents, vasodilators, and statins. 3,4 Atorvastatin, the most widely used statin, in addition to its beneficial lipid modulation effects, exerts a variety of several so-called pleiotropic actions such as inhibiting inflammation, antiventricular remodeling, improving vascular endothelial function, and antioxidant effects. 5 Because of the multiple functions, atorvastatin therapy is associated with a significant reduction in cardiovascular morbidity and mortality both in primary and secondary prevention.…”
Section: Introductionmentioning
confidence: 99%